Space radiation estimation for the Turkish lunar mission - Bektaşoğlu, Burak (My University, 2022)
One of the biggest challenges for space missions is space radiation effects. Space radiation is very dangerous to the health of astronauts on manned missions and can cause spacecraft electronic systems and solar panels to malfunction. It can even cause a task to be terminated. For this reason, the situation that the spacecraft will be in during the mission should be well known. Therefore, various simulations and tests must be performed to prepare for the space mission. In this way, precautions are taken in a way that electronic components and astronauts can withstand. The trajectory used in space missions should be determined in such a way that it best suits the purpose of the mission and that the spacecraft is exposed to the lowest possible radiation dose. Because the less radiation the spacecraft will be exposed to, the easier it will be to take precautions on the spacecraft and reduce the cost of the mission. In this study, a radiation environment simulation was made for the 2023 Turkish Lunar Mission to be carried out within the scope of the National Space Program. First, an estimated mission profile for the 2023 Lunar Mission was designed and a trajectory simulation was made. Second, data on the space particle environment on orbit were obtained for the estimated date of the mission. In addition, a model satellite was designed to be used in simulations. Finally, the particle flux data and the modeled satellite were used in the Geant4 simulation. The simulation found the radiation dose rate that the satellite will be exposed to in the 2023 Turkish Lunar Mission.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2023
Keywords: Lunar mission; Space radiation; Space environment